How to better deliver humanitarian and social assistance in fragile settings | "From fragility to stability" - Goldberg, Mark Leon; Abay, Kibrom A.; McTough, Mitchell; Sandstrom, Susanna (Global Dispatches, 2024)
Today’s episode is produced in partnership with the CGIAR Research Initiative on Fragility, Conflict, and Migration for a series that examines what works to improve the well-being of people in Fragile and Conflict Affected Settings. CGIAR is a global partnership that unites international organizations engaged in research about food security.